FORMULASI HAIR TONIC KOMBINASI EKSTRAK BUNGA SEPATU (Hibiscus rossa sinensis L.) DAN DAUN SELEDRI (Apium graveolens L.) SEBAGAI PERANGSANG PERTUMBUHAN RAMBUT PADA KELINCI (New Zealand White) - Qurrota'Ain, Rusyda; Wicahyo, Septian Maulid; Fitriawati, Anna (Jurnal Buana Farma, 2025)
Hair plays an essential role not only as protection for the scalp but also as an aesthetic element that influences appearance. One way to maintain hair health is through the use of hair tonic, a liquid cosmetic preparation formulated to care for and stimulate hair growth. This study aimed to formulate and evaluate the effectiveness of a hair tonic combining hibiscus (Hibiscus rosa-sinensis L.) and celery (Apium graveolens L.) extracts, both of which are traditionally recognized for their bioactive compounds that promote hair growth. The extracts were obtained by maceration using 96% ethanol and formulated into three concentration variations: F1 (2.5%:7.5%), F2 (5%:5%), and F3 (7.5%:2.5%). The experiment was conducted using male New Zealand White rabbits, with hair growth observed for 28 days, while physical quality parameters such as organoleptic properties, homogeneity, pH, and viscosity were also evaluated. The results showed that all formulas met the physical quality requirements of hair tonic, but differences in effectiveness were observed between formulas. Formula II (5%:5%) produced the most optimal effect, with an average hair length of 16.86 mm, outperforming Formula I (15.39 mm) and Formula III (13.39 mm), and approaching the positive control (17.89 mm). These findings highlight that the balanced combination of hibiscus and celery extracts provides a synergistic effect on hair growth. In conclusion, the formulated hair tonic not only demonstrated stability and compliance with physical standards but also offers novelty as a natural alternative that may be safer than synthetic minoxidil-based products.